Germinação de diásporos e micropropagação da sempre-viva Paepalanthus chiquitensis Herzog (Eriocaulaceae) - Magalhães, Carollayne Gonçalves (2018)
CHAPTER I: In science and common sense there is a certain rhetoric that species occurring or being distributed in very particular environments are difficult to cultivate ex situ due to the difficulties of meeting the demands, guaranteed under natural conditions. Accumulated information from six years of research with Paepalanthus chiquitensis Herzog revealed the ability of the species to propagate under ex situ conditions, producing individuals capable of reproducing sexually. It would not be a research with such relevant results if the species were not distributed in the ruptured fields of the José Ângelo Rizzo Biological Reserve / Serra Dourada State Park, GO, a phytophysiognomy marked by presenting difficult edaphoclimatic conditions to reproduce in cropping systems such as rugged topography , high altitude (between 800 and 1,200 m) and rocky outcrops with shallow, acidic and nutrient-poor soils. This research was the great stimulus and reference for chapters 2 and 3 of this dissertation, which discuss aspects of the germination process and micropropagation, respectively. CHAPTER II: Herbaceous species, Paepalanthus chiquitensis Herzog is one of the representatives of the Eriocaulaceae family with a high degree of endemism in the Brazilian rock fields. Studies on the germination and emergence of P. chiquitensis seedlings may contribute to the knowledge of reproductive, regeneration, conservation and management strategies in naturally occurring environments, while offering subsidies for the production of seedlings, either of the same species or of other endemic evergreens. In this sense, this work analyzed different treatments for the germination of the species, making a relation with the germination measures. The experiment was conducted with 13 treatments for germination: five thermal shocks for 30 minutes (35,0°C/34,7 ± 1,1 oC, 40,0/40,0 ± 1,2 oC, 50,0°C/50,3 ± 0,8 oC, 60°C/59,6 ± 2,4 oC e 70,0°C/67,6 ± 1,1 oC, imbibition for four hours in three gibberellic acid concentrations(100, 200 e 300 mg L-1de GA3), a concentration of potassium nitrate (0,2% KNO3) and distilled water (control), in addition to three controls (light diaspores, dark and mixture of light with dark diaspores). In the thermal treatments and in the controls, the diaspores did not undergo any previous soaking. The treatments analyzed do not alter the germination measures except for the synchrony, using the concentration of 300 mg L-1 of GA3and in the control, with the use of clear diaspores. It was found that P. chiquitensis diaspores present high thermal resistance at high temperatures. The presence of stimulators during imbibition, GA3 and KNO3, was not able to accelerate the germination and the use of clear diaspores promotes greater homogeneity and synchrony in the germination process. CHAPTER III: The in vitro establishment of native ornamental species from seeds has been applied in the sense of avoiding the elimination of individuals, minimizing the impacts on natural populations. There are no reports in the literature on the micropropagation of Paepalanthus chiquitensisHerzog, an evergreen with unique characteristics distributed in the rupestrian field of the José Ângelo Rizzo da Serra Dourada Biological Reserve in Mossâmedes-GO. These results will serve as a basis not only for future research on the species but also for the multiplication of evergreens at risk of extinction. The experiments were carried out in three stages, firstly, an experiment was carried out for diasporic disinfestation with solutions containing commercial sodium hypochlorite (NaClO) (5, 10, 30 and 50%). The second step involved the use of different cytokinins (2iP, BAP, TDZ and KIN) and an auxin (ANA) in the in vitro multiplication phase, all at a dosage of 1 mg L1. The third step was used ANA concentrations with the presence of activated carbon for in vitro rooting. In the in vitro establishment, the solution containing 30% commercial sodium hypochlorite was the most efficient for the disinfestation of P.chiquitensis diaspores and allowed better germinability. Although the species can develop without the presence cytokinins or exogenous auxins in the culture medium, the use of 2iP associated to the ANA in the multiplication phase, allowed greater growth of the aerial part and in the rooting the concentration of 0,25 mg L-1of ANA together with activated carbon, allowed the best results for the root system.